(3cJGH aj GdCOHs - (3nerYneQ Hf GdeKfi GdJjej HGdhdGA, GdHUQj, CHh YHjO GdfMhj,J (B209 (3g` s
(3ChdgG (B:s
(3bGd CHhYHjOI eYeQ Hf GdeKfi GdJjej, Jje bQjT, ehdi dge(B: (3cGf GdYQH GdYcGXjhf dG jYOhf s
(3BNQgG (B:s
(3GdeWYehf aj GdeMd, GdCfUGQ bGdhG(B: (3fYe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3gfGc Tc aj fSHI GdeNWhW ddeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B309s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B139 s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT (B- (3HJfg (B(3/1754) s
Keywords: (3GdCOHs